Cunningham, Chantrey and Gibbons: winged words on nation and nature, c. 1829–57. (1st December 2020) - Edwards, Jason; Harris, Amy; Sullivan, M. G.
Abstract : In this article, the authors explore the nineteenth-century British reception of Gibbons through a number of closely related images, objects and texts, frequently focusing on the bodies of dead birds. The article commences with Allan Cunningham's pivotal 1830 account of Gibbons at the start of his Lives of the Most Eminent Sculptors, which made the influential claim that the sculptor was the heir to a 'natural' decorative carving tradition and father to an indigenous British school, resistant to the idealism and allegory that characterized continental classicism. The authors go on to explore Gibbons's key status in Francis Chantrey's contemporaneous Woodcocks (c. 1829–34) for Holkham Hall, which employed Gibbons's idiom to emphasize Chantrey's related status as a paradigmatic British sportsman and sculptor. The article then examines how these characterizations of Gibbons took hold at the mid-century Great Exhibitions and at the Victoria and Albert Museum, before concluding with a close reading of an obscure, but deeply revealing 1857 meditation on Chantrey's Woodcocks, and on Gibbons before him, that reveals the complex attitudes the Victorians had in relation to the spectacle of dead animals.